Effect of fortified palm oil on growth performance, health and financial losses related to mortality of Rabbits ... - Vidjannagni, Delphin Sévérin; SEIBOU TOLEBA, Soumanou; Mahamadou, Dahouda; SINA, HAZIZ; Adenile, Adam; TOVIWAKOU, R.; TITO, U.; Harouna, Aminatou; BABA-MOUSSA, LAMINE; Natonnagnon, Ulrich (My University, 2017)
The perceptible growth delays and financial losses in the Beninese cuniculture farms are often the result of inadequate feeding and high mortality rates. The aim of this study was to contribute to improve the zootechnical performances and the profitability of the cuniculture farms. Thus, a trial was carried out on four lots of 28 rabbits (male and female) aged from 35 to 40 days with homogeneous average weights (456.155±0.355 g). Each lot was fed with a specific amount (0%, 1%, 3% and 5%) of food supplied with palm oil. After 63 days of experimentation, no difference (p>0.05) was observed between ingestions, daily average gain and consumption indices of the different lots. However, during the last five weeks of the experiment, there was recorded higher (p<0.05) intake among animal fed with 3% of palm oil (93.06 g) in comparison to those fed with a supply of 0% (85.74 g), 1% (88.49 g) and 5% (91.31 g). Considering, the initial tested animal number, the average mortality rate recorded is equivalent to 12.5%. The health risk indexes of the four foods were as follows: 46.43% (+0% of palm oil), 28.59%(+1% of palm oil), 10.74%(+3% of palm oil) and 17.41% (+5% of palm oil). To end, the minimum financial losses related to mortality in lot feed without palm oil supply (0%) were equivalent to 46.72% of total (~16696FCFA) where30.77% (+1% of palm oil), 8.45% (+3% of palm oil) and 14.06% (+5% of palm oil) were recorded for the other lots. The palm red oil (at 3%) contributes to the improvement of animal health and reduces financial losses related to mortality.
Keywords: Rabbits; Red palm oil; Zootechnical performances; Mortality